Continent-scale global change attribution in European birds - combining annual and decadal time scales - Jørgensen, Peter Søgaard; Böhning-Gaese, Katrin; Thorup, Kasper; Tøttrup, Anders P; Chylarecki, Przemysław; Jiguet, Frédéric; Lehikoinen, Aleksi; Noble, David G; Reif, Jiri; Schmid, Hans; van Turnhout, Chris; Burfield, Ian J; et al. (Global change biology, 2016)
Species attributes are commonly used to infer impacts of environmental change on multiyear species trends, e.g. decadal changes in population size. However, by themselves attributes are of limited value in global change attribution since they do not measure the changing environment. A broader foundation for attributing species responses to global change may be achieved by complementing an attributes-based approach by one estimating the relationship between repeated measures of organismal and environmental changes over short time scales. To assess the benefit of this multiscale perspective, we investigate the recent impact of multiple environmental changes on European farmland birds, here focusing on climate change and land use change. We analyze more than 800 time series from 18 countries spanning the past two decades. Analysis of long-term population growth rates documents simultaneous responses that can be attributed to both climate change and land-use change, including long-term increases in populations of hot-dwelling species and declines in long-distance migrants and farmland specialists. In contrast, analysis of annual growth rates yield novel insights into the potential mechanisms driving long-term climate induced change. In particular, we find that birds are affected by winter, spring, and summer conditions depending on the distinct breeding phenology that corresponds to their migratory strategy. Birds in general benefit from higher temperatures or higher primary productivity early on or in the peak of the breeding season with the largest effect sizes observed in cooler parts of species' climatic ranges. Our results document the potential of combining time scales and integrating both species attributes and environmental variables for global change attribution. We suggest such an approach will be of general use when high-resolution time series are available in large-scale biodiversity surveys.
Keywords: Population Density; Animals; rozmnožování; biodiverzita; Birds; Climate Change; Europe; teoretické modely; Seasons; Animal Migration; klimatické změny; zemědělství; Reproduction; Evropa; hustota populace; roční období; ptáci; dieta; Diet; Biodiversity; migrace zvířat; zvířata; Models, Theoretical; Agriculture